Counseling on the Function of Vitamins in Increasing Body Endurance and Training on Hand Washing Movements, Wearing Masks, and Keeping Distance to the Marching Band Genta Bhuwana Ganeswara - Ananta, I Gusti Bagus Teguh; Anjasmara, Dewa Gede Anom; Indrayoni, Putu (Jurnal Abdimas ITEKES, 2021)
Various preventive measures in tackling the increase in COVID-19 cases must be carried out, both by the government and the community. Preventive efforts are so far the best practice to reduce the impact of the COVID-19 pandemic, given that there is no treatment that is considered effective against the SARS-CoV-2 virus. One of the government's efforts to overcome the impact of the COVID-19 pandemic is by implementing the 3M movement, namely washing hands, wearing masks, and maintaining distance. Marching band is one of the art and sports learning activities that have been the impacted by the COVID-19 pandemic. Music learning methods in the classroom can be done online, but in practice mastery of musical instruments needs to be done offline. The offline training process needs to get more attention by implementing the 3M protocol, namely maintaining distance, using masks, and washing hands. Based on this, counseling activities on the function of vitamins were carried out in increasing endurance as well as training in washing hands, wearing masks, and keeping a distance. The implementation was carried out by conducting counseling and training which was attended by 25 participants. The results of the activity showed that there was an increase in the knowledge of the training participants regarding the COVID-19 pandemic and the movement to wash hands, wear masks and keep a distance, >80% of Marching Band members Genta Bhuwana Ganeswara had good knowledge.